AB1097 The Impact of Systemic Lupus Erythematosus on Work Productivity: Data from Patients from the Province of Cordoba, Argentina. (9th June 2015) - Bertoli, A.; Lόpez Pérez, M.J.; Alba, P.; Albiero, A.; Albiero, E.; Alessio, D.; Albarelos, A.; Asbert, P.; Astesana, P.; Audisio, M.; Benzaquén, N.; Castaños Menescardi, M.S.; et al.
Abstract : Background: Since SLE tends to occur during the productive years of life, the cost of the disease derives not only from direct health expenditures but also from the impact the disease has on work productivity. Objectives: To describe the impact of SLE on work productivity and to assess the factors influencing this outcome measure. Methods: We studied 225 patients (1987 ACR criteria), age ≥16 years. Work productivity was assessed with the WPAI:Specific Health Problem for SLE. The WPAI yeilds four scores: % work time missed, % of impairment at work, % of overall work impairment and % of non-work related activity impairment. The relationship between socioeconomic-demographic, self-reported quality of life (as per the Lupus PRO), clinical data [clinical manifestations, diagnostic criteria (1987 ACR criteria), disease activity (SELENA-SLEDAI), damage (SLICC Damage Index), co-morbidities (Charlson Index)] and the four scores of the WPAI was examined with the Man-Whitney U test and Spearman's Rho test. Variables with p≤0.10 in these analyses were then entered in a multivariable linear regression with each score of the WPAI as the dependent variable. Results: Patients were predominantly females (89%) and they had a median (IQR) age at diagnosis of 26.0 (16.0) years. Median (IQR) disease duration was 96.0 (144.0) months. Median (IQR) percentage of work time missed was 0.0 (25.0)%, of impairment at work was 10.0 (56.0)%, of overall work impairment 0.0 (56.0)% and of activity impairment 40.0 (60.0)%. Variables significant in both, the univariable and multivariable analyses, are shown in Table below Conclusions: While work productivity is not largely affected in this sample of patients, non-work related activities seems to have a much greater impact in SLE. Patients with a higher disease activity and number of co-morbidities and a lower self-perceived quality of life are at higher risk for work productivity impairment Disclosure of Interest: None declared